Description of Knowledge Level of Prevention of Skin Hyperpigmentation in Adolescents - Nida Alhusna Ashar; Wahyu Riyaningrum (UM Purwokerto Press, 2022)
Background: Sunlight is a source of energy that plays an important role in the life of all living things on earth. In addition to its positive effects, excessive exposure to high-intensity sunlight can cause skin hyperpigmentation, make skin dull and flaky, and can even increase the risk of skin cancer. Aim: To describe the level of knowledge on prevention of skin hyperpigmentation in adolescents. Methods: This research is a quantitative descriptive study with a cross-sectional study approach. The population and sample used were students of class XI at SMK Muhammadiyah 1 Purbalingga with a total sample of 80 people. Results: The majority of respondents were female as many as 43 at 53.8%. Meanwhile, seen from the age of the respondents in the age range of 15-17 years with a mean of 16.39 and a standard deviation of 0.515. The level of knowledge of respondents regarding the prevention of skin hyperpigmentation was mostly in the moderate category with a male percentage of 43.5% and female 56.5%, good category with a male percentage of 43.5% and female 56.5%, while less knowledge category with the percentage of men 50% and women 50%. Conclusion: The level of knowledge on preventing skin hyperpigmentation in adolescents is in the sufficient category.